ISLAMIC ECONOMIC RESILIENCE IN THE DYNAMICS OF MODERN ECONOMY: A SYNTHESIS OF BEEKUN AND CHAPRA'S THOUGHTS - Endang Jumali; Fitriyani (UIN Sunan Gunung Djati Bandung, 2025)
Economic resilience is essential in responding to the instability and inequality that often occurs in the modern economy. The Islamic economic perspective offers an alternative approach that emphasizes the material aspect and the integration of moral, social, and spiritual values ​​in building economic resilience. This article aims to examine the concept of economic resilience in the thoughts of two contemporary Islamic economic figures, Rafik Issa Beekun and M. Umer Chapra, and to synthesize their views to formulate an Islamic economic resilience model relevant to the dynamics of the current global economy. The research method used is library research with a qualitative-descriptive approach. Data were obtained from both the main works of figures and relevant supporting literature. The study results show that Beekun emphasizes the importance of individual ethics, social balance, and collective responsibility in building economic resilience. Meanwhile, Chapra focuses on reforming the economic institutional system, fair distribution of wealth, and the active role of the state in maintaining financial stability. The synthesis of their thoughts produces a multidimensional Islamic economic resilience model, integrating individual ethical values, the Sharia economic policy system, and fair state governance. The implication for the dynamics of the modern economy lies in the opportunity to build a more humane, inclusive, and sustainable economic system as an alternative to the moral crisis and inequality in the global capitalist system.